2022
DOI: 10.3390/ijerph191912095
|View full text |Cite
|
Sign up to set email alerts
|

Using Convolutional Neural Networks to Derive Neighborhood Built Environments from Google Street View Images and Examine Their Associations with Health Outcomes

Abstract: Built environment neighborhood characteristics are difficult to measure and assess on a large scale. Consequently, there is a lack of sufficient data that can help us investigate neighborhood characteristics as structural determinants of health on a national level. The objective of this study is to utilize publicly available Google Street View images as a data source for characterizing built environments and to examine the influence of built environments on chronic diseases and health behaviors in the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Adams et al found that a deep learning approach applied to Google Street View was able to classify microscale features of pedestrian streetscapes (e.g., sidewalks, walk signals) with >84% accuracy compared to human annotation [25]. Yue et al [49] also applied convolutional neural networks to Google Street View and found validation accuracy of >82% for environmental features and subsequently linked those predicted built environment features with chronic conditions and mental health [48]. Given the diminishing cost of image/video data collection and storage, image-based analyses may provide important contextual information for obesity-related research, including nutrition and physical activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…Adams et al found that a deep learning approach applied to Google Street View was able to classify microscale features of pedestrian streetscapes (e.g., sidewalks, walk signals) with >84% accuracy compared to human annotation [25]. Yue et al [49] also applied convolutional neural networks to Google Street View and found validation accuracy of >82% for environmental features and subsequently linked those predicted built environment features with chronic conditions and mental health [48]. Given the diminishing cost of image/video data collection and storage, image-based analyses may provide important contextual information for obesity-related research, including nutrition and physical activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…We used data described by Nguyen and colleagues . The data consisted of 164 million images extracted from Google Street View’s Application Programming Interface from November 1 to 30, 2019.…”
Section: Methodsmentioning
confidence: 99%
“…We used data described by Nguyen and colleagues. 23,27,29 The data consisted of 164 million images extracted from Google Street View's Application Programming Interface from November 1 to 30, 2019. Convolutional neural networks-the state-of-art model for computer vision tasks-were used to identify objects in the collected images.…”
Section: Built Environment Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Street view applications make it efficient to address various issues related to on-site crime. Deng et al (2022), He et al (2017), Jing et al (2021), Khorshidi et al (2021), Kondo et al (2017), Naik et al (2014), Sas et al (2022), Sytsma et al (2021), Zhou et al (2021) and Yue, Antonietti, et al (2022) utilised street view images to discern the characteristics of the built environment for drug activities and street robberies. These studies empirically support the broken window theory and reveal that built environments induce crime and violence.…”
Section: Review and Applicationsmentioning
confidence: 99%